Impact of Contact With Grandparents on Children's and Adolescents' Views on the Elderly. Issue 4 (19th December 2017) - Flamion, Allison; Missotten, Pierre; Marquet, Manon; Adam, Stéphane
Abstract : Stereotypes, prejudice, and discrimination against the elderly (ageism) may manifest themselves in children at an early age. However, the factors influencing this phenomenon are not well known. Using both explicit and open‐ended questions, this study analyzed the influence of personal and familial parameters on the views of 1, 151 seven‐ to sixteen‐year‐old Belgian children and adolescents on the elderly. Four factors were found to affect these views: gender (girls had slightly more positive views than boys), age (ageism was lowest in 10‐ to 12‐year‐old, reminiscent of other forms of stereotypes and cognitive developmental theories), grandparents' health, and most importantly, quality of contact with grandparents (very good and good contacts correlated with more favorable feelings toward the elderly, especially in children with frequent contacts).